Value of BIOCHIP technology in the serological diagnosis of pemphigoid gestationis - Sadik, Christian David; Bohlmann, Michael K. (Acta dermato-venereologica, 2017)
Abstract is missing (Short communication)
Epub ahead of print May 13, 2016
Gesehen am 07.06.2018